2019
DOI: 10.1097/01.hs9.0000560796.93881.5c
|View full text |Cite
|
Sign up to set email alerts
|

Pf628 O-12-M1: An Evaluation of Time to Next Treatment in Melflufen and Dexamethasone-Treated Patients With Relapsed/Refractory Multiple Myeloma

Abstract: Nausea/Vomiting and Diarrhea subscales, while consistently worse for ixazomib than placebo (LS mean [95% CI] change at interval 24, 5.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The Phase II part assessed the activity of melflufen in 45 patients with late-stage RRMM who had received a median of four prior lines of treatment and who were refractory to both lenalidomide (an IMiD) and bortezomib (a PI). Melflufen + dexamethasone treatment resulted in disease stabilization in the majority of patients, with a favorable median time to next treatment and ORR [26]. Furthermore, the clinical response observed in this study was durable, which is promising given the advanced nature of the disease in these patients [26].…”
Section: Clinical Development Of Melflufenmentioning
confidence: 58%
See 1 more Smart Citation
“…The Phase II part assessed the activity of melflufen in 45 patients with late-stage RRMM who had received a median of four prior lines of treatment and who were refractory to both lenalidomide (an IMiD) and bortezomib (a PI). Melflufen + dexamethasone treatment resulted in disease stabilization in the majority of patients, with a favorable median time to next treatment and ORR [26]. Furthermore, the clinical response observed in this study was durable, which is promising given the advanced nature of the disease in these patients [26].…”
Section: Clinical Development Of Melflufenmentioning
confidence: 58%
“…Melflufen + dexamethasone treatment resulted in disease stabilization in the majority of patients, with a favorable median time to next treatment and ORR [26]. Furthermore, the clinical response observed in this study was durable, which is promising given the advanced nature of the disease in these patients [26]. The safety profile of melflufen in the O-12-M1 study demonstrated predictable and manageable adverse events (AEs), with the most common being grade 3 and 4 hematological AEs and low rates of non-hematological AEs [26].…”
Section: Clinical Development Of Melflufenmentioning
confidence: 98%
“…Melflufen is generally well tolerated, with the most common grade 3–4 AEs being hematologic and low frequencies of non-hematologic AEs [ 1 , 41 , 45 , 46 ]. While rates of neutropenia (54–79%), thrombocytopenia (63–76%), and anemia (43%) were high, grade 3 (1–16%) and 4 (0–3%) bleeding events are low [ 2 , 42 ].…”
Section: Melflufenmentioning
confidence: 99%